2016
DOI: 10.1111/evj.12545
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quantitative polymerase chain reaction for equine herpesvirus‐5 in blood, nasal secretions and bronchoalveolar lavage fluid for the laboratory diagnosis of equine multinodular pulmonary fibrosis

Abstract: Although histopathological confirmation (lung biopsy) is considered the gold standard for EMPF diagnosis, results of qPCR testing of BALF or a combination of whole blood and nasal secretions should be regarded as clinically useful in support of this diagnosis. The latter testing may be relevant when dealing with horses in respiratory distress, for which invasive procedures such as BALF collection or lung biopsies may be detrimental to their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 20 publications
(40 reference statements)
1
26
0
Order By: Relevance
“…Equine herpesvirus‐5 has been associated with the development of multinodular pulmonary fibrosis (EMPF), herpetic ocular disease, and lymphoma in horses, however, these diseases are rare while of EHV‐5 shedding in the equine population is common . It has previously been reported that horses with nasal secretion viral loads of >650 000 gB genes/million cells were more likely to have EMPF than controls . Interestingly, 38.2% of EHV‐5 qPCR positive horses in our study were shedding >650 000 gB genes/million cells.…”
Section: Discussionmentioning
confidence: 99%
“…Equine herpesvirus‐5 has been associated with the development of multinodular pulmonary fibrosis (EMPF), herpetic ocular disease, and lymphoma in horses, however, these diseases are rare while of EHV‐5 shedding in the equine population is common . It has previously been reported that horses with nasal secretion viral loads of >650 000 gB genes/million cells were more likely to have EMPF than controls . Interestingly, 38.2% of EHV‐5 qPCR positive horses in our study were shedding >650 000 gB genes/million cells.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical signs occur in several respiratory diseases in horses. In a study on the detection of EHV-5 in horses with EMPF and other respiratory diseases, the clinical signs observed in different groups were similar (Pusterla et al 2015), thus demonstrating their non-specificity. EMPF is difficult to diagnose in a living animal and may be suspected based on clinical and radiological examination, lung biopsy, and identification of EHV-5 by tracheal lavage with PCR analysis (Williams et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, some agents such has EHV5 or intracellular bacteria are not always easily isolated (Allam and Lemcke ; Pusterla et al . ). The mare also had a history of strangles and was not adequately vaccinated.…”
Section: Discussionmentioning
confidence: 97%
“…Pulmonary biopsy, naso-pharyngeal swab and transtracheal wash cytology and bacteriology could not establish the aetiology of the respiratory distress and the pulmonary fibrosis. However, some agents such has EHV5 or intracellular bacteria are not always easily isolated (Allam and Lemcke 1975;Pusterla et al 2015). The mare also had a history of strangles and was not adequately vaccinated.…”
Section: Complementary Examinationsmentioning
confidence: 99%